TRPA1 mediates ozone-induced murine model of COPD through the Wnt5a/GSK-3β/β-catenin pathway. - Xie,M; Chang,Q; Li,C; Liu,Q; Weng,J; Feng,Y; Zhang,H; Li,M; Chung,KF; Adcock,IM; Fan,X; Li,F (Environ Pollut, 2026)
Ambient ozone (O3), a ubiquitous oxidant gas and key component of photochemical smog, damages the airway epithelium, provokes oxidative stress, and sustains chronic inflammation, which favors the onset and advancement of chronic obstructive pulmonary disease (COPD). Yet the molecular sensors linking long-term ozone exposure to COPD remain incompletely defined. We examined whether the oxidant-sensitive channel Transient receptor potential ankyrin 1 (TRPA1) mediates ozone-driven murine model of COPD through the Wnt5a/GSK3β/β-catenin pathway. C57BL/6J or TRPA1-deficient mice underwent ozone exposure (2.5 ppm, 3 h/session) every 3 days for 2 months, following administration of either the TRPA1 antagonist A967079 or the Wnt5a/GSK3β/β-catenin inhibitor XAV-939. Similarly, BEAS-2B cells treated with A967079 or XAV-939 or TRPA1-silenced cells were subjected to ozone (1 ppm, 3 h/day) for 4 consecutive days. Oxidative stress, inflammatory responses, emphysematous changes, mitochondrial dysfunction, and airway remodeling were assessed. In addition, gene set variation analysis (GSVA) was used to quantify Reactome Wnt5a/GSK3β/β-catenin pathway activity through public COPD transcriptomic cohorts. Pharmacological inhibition or genetic deficiency of TRPA1 significantly attenuated ozone-induced lung function impairment, and ozone-triggered oxidative stress, emphysematous changes, mitochondrial dysfunction, and airway remodeling. Notably, pharmacological suppression of the Wnt5a/GSK3β/β-catenin pathway using XAV-939 produced comparable protective effects to TRPA1 blockade in both ozone-exposed murine models and BEAS-2B cells. GSVA demonstrated tissue-specific associations between TRPA1 and Wnt5a/GSK3β/β-catenin pathway in COPD patients. TRPA1 mediates crucially ozone-induced COPD through modulation of the Wnt5a/GSK-3β/β-catenin signaling. Therapeutic targeting of both TRPA1 and Wnt5a/GSK3β/β-cat